Apa Penyebab Utama Insomnia pada Mahasiswa Kedokteran Tahun 2017-2024: Literature Review - Gusti Ayu Audya Varygata Masta; I Komang Gunawan Landra; Nyoman Intan Permatahati Wiguna (Lembaga Pengembangan Kinerja Dosen, 2026)
Insomnia is one of the most prevalent sleep disorders among medical students, characterized by difficulties in initiating or maintaining sleep that affect concentration and academic performance. This literature review aims to identify the main factors contributing to insomnia among medical students from 2017 to 2024. Articles were obtained from PubMed, Google Scholar, and Garuda databases using the keywords “insomnia,” “medical students,” and “sleep quality.” A total of seven studies met the inclusion and exclusion criteria. The results indicate that insomnia in medical students is a multifactorial problem influenced by academic stress, excessive internet use, poor sleep habits, and psychological conditions such as anxiety and depression. Academic stress and irregular study schedules were found to increase sympathetic nervous system activation, reducing melatonin production and impairing sleep quality. Furthermore, excessive screen exposure and internet addiction contributed to delayed sleep onset. These findings highlight the need for early interventions, including stress management programs and good sleep hygiene education, to improve the well-being and academic performance of medical students.